Blackness as a dialogical construct in Toni Morrison's fiction - Fernández, Silvia Lucía (2006)
Identity can be defined in terms of an ideological relationship with others, especially “significant others”, that generally mirror back an image of the self in question within a social context. The human mind is not monological; therefore, we define identity in a dialogue with or a struggle against others. This paper presents how the identity of black female children in Toni Morrison’s The bluest eye (1994) is dialogically built up within a context that is American, canonical and whose literary supremacy is eminently white.